Homeopathic Medicines in Third (Omicron) Wave of COVID-19: Prognostic Factor Research - Manchanda, Raj Kumar; Miglani, Anjali; Kalsi, Amrit; Brahmachari, Smita; Rama, Kamsali Nadigadda; Goel, Pawan; Kaushik, Pallavi; Jethani, Anju; Nagrath, Cheshta; Pangtey, Nirmal Yadav; Kannoth, Jithesh Thavarayil; Sharma, Kavita; Arora, Shelly; Amitav, B.; Roy, Pradip Kumar; Kudiyarasu, Ram Kumar; Rutten, Lex (Homeopathy, 2023)
Background With the emergence of new variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, such as the Omicron variant, during the third wave of the coronavirus disease 2019 (COVID-19) pandemic, there was a need to identify useful homeopathic medicines. This study aimed to identify such medicines and their indications using prognostic factor research (PFR).Methods This was an open-label, multi-centred observational study conducted in January 2022, on confirmed COVID-19 cases. The data were collected from integrated COVID Care Centres in Delhi, India, where homeopathic medicines were prescribed along with conventional treatment. Only those cases that met a set of selection criteria were considered for analysis. The likelihood ratio (LR) was calculated for the frequently occurring symptoms of the frequently prescribed medicines. An LR of 1.3 or greater was considered meaningful.Results Out of the 362 COVID-19 cases, 263 cases were selected for analysis after applying selection criteria. Common symptoms included fatigue, cough, sore throat, myalgia and headache. Twenty-one medicines were prescribed, of which nine medicines – Gelsemium sempervirens, Bryonia alba, Hepar sulphuris, Rhus toxicodendron, Pulsatilla nigricans, Arsenicum album, Belladonna, Nux vomica and Phosphorus – were frequently used. By calculating LRs, the study identified meaningful indications for these medicines.Conclusion Homeopathic medicines have shown promising results in the third wave of COVID-19 as an adjunct therapy. The medicines that were used in the first and second waves were found useful in the third wave also, and their indications were analogous to those found in the earlier waves. Certain new indications of some medicines were elicited in this wave, which warrant further research. However, it is important not to restrict to these medicines only and to continue data collection on COVID-19 in future waves for the improvement of the COVID-19 mini-repertory.
Keywords: COVID-19; third wave; homeopathy; prognostic factor research; likelihood ratio